2021
DOI: 10.3389/fcvm.2021.753133
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Systemic Immune-Inflammation Index With Short-Term Mortality of Congestive Heart Failure: A Retrospective Cohort Study

Abstract: Purpose: The present study aimed to clarify the potential predictive significance of Systemic immune-inflammation index (SII) in assessing the poor prognosis of critically ill patients with congestive heart failure (CHF).Methods: Detailed clinical data were extracted from the Multiparameter Intelligent Monitoring in Intensive Care III database after gaining access and building the local platform. The 30- and 90-day and hospital all-cause mortalities of the patient was the primary outcome, and the readmission r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…HCC patients with SII ≥ 330 × 10 9 /L had higher recurrence rates and shorter survival time than patients with SII < 330 × 10 9 /L. In a retrospective cohort study of 4606 critically ill patients with CHF, high levels of SII could effectively predict high 30- and 90-day and hospital mortalities, as well as the high risk of occurrence of major cardiovascular adverse events (MACEs) [ 16 ]. In a study of 4381 patients, Jiang et al [ 19 ] demonstrated that elevated SII levels were independently associated with increased risk of CI-AKI in patients undergoing coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC patients with SII ≥ 330 × 10 9 /L had higher recurrence rates and shorter survival time than patients with SII < 330 × 10 9 /L. In a retrospective cohort study of 4606 critically ill patients with CHF, high levels of SII could effectively predict high 30- and 90-day and hospital mortalities, as well as the high risk of occurrence of major cardiovascular adverse events (MACEs) [ 16 ]. In a study of 4381 patients, Jiang et al [ 19 ] demonstrated that elevated SII levels were independently associated with increased risk of CI-AKI in patients undergoing coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
“…Based on PLT, neutrophils and lymphocytes, SII has the advantage of low cost and convenience and can simultaneously reflect the inflammatory and immune status of patients [ 15 ]. Its role in predicting clinical outcomes in cardiovascular disease [ 16 , 17 ], malignancy survival [ 15 , 18 ] and the incidence of contrast-induced acute kidney injury (CI-AKI) [ 19 ] has been demonstrated. Despite these observations, to the best of our knowledge, no epidemiological study to date has explored the prognostic effect of the SII in critically ill patients with AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have already described it as a prognostic marker in appendicitis [ 65 ], coronary artery disease [ 66 ] and neoplasms [ 67 , 68 ]. Patients with a high level of SII had a significantly higher mortality rate than those with a low SII [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with myocardial infarction, an increased NEU could be used to predict the development of AHF ( 38 ), while both a decreased and an increased PLT were associated with an increased mortality in a “U”-shaped relationship ( 16 ). CBC-derived parameters such as NLR, PLR, LMR and SII have also been extensively studied and proven to be highly-sensitive biomarkers of the disease, which could reveal the alterations in the immunological balance due to various pathologies and were shown to be associated with the prognosis in patients with AHF ( 18 21 , 39 ).…”
Section: Discussionmentioning
confidence: 99%